2009
DOI: 10.1016/j.ajog.2009.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Do multivitamin supplements modify the relationship between prenatal alcohol intake and miscarriage?

Abstract: Objective-To determine whether multivitamin supplements modify the relationship between alcohol consumption during pregnancy and the risk of miscarriage.Study Design-We utilized data from a population-based cohort study of pregnant women (n=1061; response rate=39%). Participants were asked about their alcohol consumption and vitamin intake during pregnancy.Results-Among multivitamin nonusers, women who drank alcohol during their pregnancy were more likely to have a miscarriage compared to women who abstained (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Existing data has documented the possibility of multiple micronutrient supplements protecting against the negative effects of fetal alcohol exposure. Research in this area is preliminary, yet the data are compelling and demonstrate the possibility of micronutrient supplementation as having a critical role in preventing FAS (Ammon Avalos, Kaskutas, Block, & Li, 2009; Avalos, Kaskutas, Block, Abrams, & Li, 2011; Ballard, Sun, & Ko, 2012). It is possible that the administration of fortified foods and micronutrient capsules during prenatal care could prevent FAS.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data has documented the possibility of multiple micronutrient supplements protecting against the negative effects of fetal alcohol exposure. Research in this area is preliminary, yet the data are compelling and demonstrate the possibility of micronutrient supplementation as having a critical role in preventing FAS (Ammon Avalos, Kaskutas, Block, & Li, 2009; Avalos, Kaskutas, Block, Abrams, & Li, 2011; Ballard, Sun, & Ko, 2012). It is possible that the administration of fortified foods and micronutrient capsules during prenatal care could prevent FAS.…”
Section: Discussionmentioning
confidence: 99%
“…Women who were more likely to drink alcohol were less likely to take multivitamin supplements in the periconceptional period. Two studies have reported that multivitamin supplementation in early pregnancy reduced the risk of preterm and small-for-gestational-age births (Avalos et al, 2011) and miscarriage (Ammon Avalos et al, 2009) among alcohol users. However, this study is the first of which we are aware that has explored associations between multivitamin use and alcohol consumption in women during the periconceptual period.…”
Section: Discussionmentioning
confidence: 99%
“…As embryonic development begins at conception, before most women are aware of their pregnancy, the benefits of multivitamin supplementation can best be obtained by supplementation that is initiated in the period prior to pregnancy (CDC, 2004; Wolff et al, 2009). However, surveys show that less than half of childbearing-aged women (Ammon Avalos et al, 2009; Kim et al, 2011; Sullivan et al, 2009) and less than one-third of women in the month prior to pregnancy (CDC, 2004; Yu et al, 1996) use multivitamin supplements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further potential confounders collected as repeated measures across all questionnaires include maternal psychological wellbeing, [26–30] smoking, [28, 31, 32] illicit substances, [27, 33] medication and supplement use, particularly folate [14, 34]. Several factors are measured in Q4 (at 12 months after birth), providing proxy measures for unknown antecedent confounding factors.…”
Section: Methodsmentioning
confidence: 99%